Cost effective polymer optical couplers based on multimode interference techniques - Ibrahim, Mohd. Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar (Romania National Institute of Research and Development for Optoelectronics, 2007)
Weakly guiding Multimode Interference (MMI) optical splitters and cross couplers based on photodefinable BenzoCyclobutene (BCB 4024-40) polymer are presented for the first time. The devices are designed based on three interference mechanisms of MMI and fabricated on BK7 glass substrate with a thin layer of SiO2 as cover. A cost effective chemical etching technique is used in the fabrication process to take advantage of the photosensitive nature of the polymer. The waveguide loss is measured using the cut-back method to be 3.5 dB/cm. The fabricated symmetric power splitters are found to exhibit 0.15-0.51 dB splitting uniformity with maximum recorded insertion loss of 1.13 dB. Meanwhile, the 2Ã—2 cross couplers are testified to demonstrate a maximum crosstalk of -17.81 dB and maximum loss of 3.37 dB.